Entosis Acts as a Novel Way within Sertoli Cells to Eliminate Spermatozoa in Seminiferous Tubule - Ahmed, Nisar; Yang, Ping; Huang, Yufei; Chen, Hong; Liu, Tengfei; Wang, Lingling; Nabi, Fazul; Liu, Yi; Chen, Qiusheng (Frontiers in Physiology, 2017)
The present study was designed to investigate the hypothesis that in vivo entosis is a novel pathway for eliminating spermatozoa in the seminiferous tubules (ST) during hibernation of the Chinese soft-shelled turtle. Western blot analysis revealed that the expression of LAMP1 in the testis was significantly higher during hibernation than that during non-hibernation. Immunohistochemistry reaction showed that LAMP1-positive substance was distributed within the Sertoli cells of the testis. Further examination by transmission electron microscopy (TEM), many degraded spermatozoa being enwrapped within large entotic vacuoles in Sertoli cells. The nucleus and the flagellum of the spermatozoa were shown to be decomposed and digested inside entotic vacuoles within Sertoli cells. More than two spermatozoa heads were always observed in each internalized vacuoles. Deserving note is that, a number of different autophagosomes, including initial autophagic vesicles and degradative autophagic vesicles were found inside the entotic vacuoles of the Sertoli cells during hibernation. At the end of hibernation, entotic vacuoles and their autophagosomes disappeared, and numerous large lipid droplets (LDs) appeared within the Sertoli cells. Adherens junctions were apparent between Sertoli cells and developing germ cells, which is the ultrastructural basis of entosis. Taken together, the results presented here show that in the turtle: 1) entosis with internal autophagosomes can take place within normal body cells during hibernation; 2) spermatozoa, as a highly differentiated cell can be internalized and degraded within Sertoli cell by entosis in vivo, which is in favor of the next reproductive cycle in the turtle.